2004
DOI: 10.1149/1.1634121
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Insertion/Removal Mechanism of LiCoVO[sub 4] in Lithium-Ion Cells

Abstract: The first charge and discharge reaction of LiCoVO 4 with a spinel structure as an anode material for a Li-ion battery was investigated. LiCoVO 4 showed a much larger reversible capacity, about 685 Ah kg Ϫ1 , compared with a commercially available graphite anode. From the X-ray diffraction measurement, the spinel structure of LiCoVO 4 where V ions reside in a tetrahedral site initially changed to an atacamite-type structure where V ions occupied an octahedral site and finally showed irreversible deformation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Subsequently, the group of Tarascon 1098,1099 studied both crystalline and amorphous (hydrated) phases of LiNiVO 4 and found that they show capacity fading from ∼1000 mA•h g −1 to ∼550 mA•h g −1 after 50 cycles. Similar capacity fading in LiNiVO 4 was also reported by Han et al 1100 Shirakawa et al 1101,1102 studied in detail the Li−LiCoVO 4 system to understand the reaction mechanism. They found that at 0.02C and at 5C rates (1C = 350 mA g −1 ), reversible capacities of 980 and 800 mA•h g −1 are obtained.…”
Section: Ternary Oxidessupporting
confidence: 76%
See 1 more Smart Citation
“…Subsequently, the group of Tarascon 1098,1099 studied both crystalline and amorphous (hydrated) phases of LiNiVO 4 and found that they show capacity fading from ∼1000 mA•h g −1 to ∼550 mA•h g −1 after 50 cycles. Similar capacity fading in LiNiVO 4 was also reported by Han et al 1100 Shirakawa et al 1101,1102 studied in detail the Li−LiCoVO 4 system to understand the reaction mechanism. They found that at 0.02C and at 5C rates (1C = 350 mA g −1 ), reversible capacities of 980 and 800 mA•h g −1 are obtained.…”
Section: Ternary Oxidessupporting
confidence: 76%
“…They found that at 0.02C and at 5C rates (1C = 350 mA g −1 ), reversible capacities of 980 and 800 mA•h g −1 are obtained. X-ray absorption spectral studies on LiCoVO 4 1101,1102 and on LiNiVO 4 1103 show that upon reaction with Li, the Co and Ni ions are reduced to metal nanoparticles, whereas V 5+ ion is reduced to only a bivalent state (V 2+ ), but not to the metal.…”
Section: Ternary Oxidesmentioning
confidence: 99%
“…Shirakawa et al have examined the first charge and discharge reaction of spinel type LiCoVO 4 in order to evaluate its potential as a possible anode material, observing a high reversible capacity of 685 mAh/g. 63 During the process, the structure was observed to change from spinel to atacamite-type, before becoming amorphous.…”
Section: Titanate Anodesmentioning
confidence: 99%
“…LiCoVO 4 possess an inverse spinel structure in which Li + and Co 2+ ion evenly reside in octahedral sites, and V 5+ ions occupy the tetrahedral sites. The Li + ions present in the octahedral site take part in the intercalation process. Despite these investigations, the application of LiCoVO 4 for Li + storage via intercalation pseudocapacitance has not been studied.…”
Section: Introductionmentioning
confidence: 99%